SOCIAL STUDIES PRE-SERVICE TEACHERS' COMPUTER SELF EFFICACY BELIEFS AND ATTITUDES ON COMPUTER-ASSISTED INSTRUCTION. - TOPKAYA, Yavuz; TANGÜLÜ, Zafer; YILAR, Bayram; ŞİMŞEK, Ufuk (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2015)
As a result of the study, social science teacher candidates' perceptions on computer-assisted instruction are positive and their computer self-efficacy beliefs are at good levels. These indicate that social science teacher candidates have positive attitudes towards computer-assisted instruction, and they trust their selves to use computers. In present study, it was aimed to measure social science preservice teachers' computer self efficacy beliefs and attitudes on computer-assisted instruction. The research group consists of 219 teacher candidates who study social science education during the 2012-2013 education year at the Kazım Karabekir College of Education in Atatürk University. This study was designed by quantitative research approach. Descriptive research method one of the correlational survey models was used. Survey research discovers characteristic attributions of a specific population. SPSS 17.0 package program, Pearson's product-moment correlation coefficient, one-way analysis of variance (ANOVA), independent groups t test, and Bonferroni post hoc technique are used in the direction of research problems. As a result of the study, social science teacher candidates' perceptions on computer-assisted instruction are positive and their computer self-efficacy beliefs are at good levels. These indicate that social science teacher candidates have positive attitudes towards computer-assisted instruction, and they trust their selves to use computers.